Analysis of the Minister of Education's Curriculum Policy in the 2019-2024 Vs. 2024-2029 Era - Supriyanti, Supriyanti; Kurniawati, Dewi; Susanto, Roni (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to analyze the implications of the policy of eliminating and reinstating the major system in Senior High Schools (SMA) on the development of students' interests and talents in Lampung Province. Using a descriptive qualitative approach and case study method, data were collected through interviews, observations, and documentation in seven senior high schools across the Lampung region. The analysis used Foucauldian Discursive Analysis (FDA) to map the policy dynamics in two government periods: 2019–2024 and 2024–2029. The study results show that the Independent Curriculum policy (2019–2024) provides a wider exploration space for students' interests and talents, but faces implementation challenges due to limited infrastructure and human resources. Meanwhile, the major reinstatement policy (2024–2029) provides a more structured learning direction, but risks narrowing students' exploration space. A comparison of the two shows that the effectiveness of the policy is highly dependent on institutional readiness and the quality of mentoring. This study recommends a hybrid approach that combines the flexibility of subject selection with the major structure as an alternative solution for a more adaptive and inclusive secondary education system.